2008
DOI: 10.1586/14789450.5.3.457
|View full text |Cite
|
Sign up to set email alerts
|

Breast tumor metastasis: analysis via proteomic profiling

Abstract: The ability to predict the metastatic behavior of a patient's cancer, as well as to detect and eradicate such recurrences, remain major clinical challenges in oncology. While many potential molecular biomarkers have been identified and tested previously, none have greatly improved the accuracy of specimen evaluation over routine histopathological criteria and, to date, they predict individual outcomes poorly. The ongoing development of high-throughput proteomic profiling technologies is opening new avenues for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 71 publications
1
5
0
Order By: Relevance
“…The data suggest that various metastasis profiles exist. This has also been shown for other tumor types by other authors [75][76][77][78][79][80][81][82][83].…”
Section: Predictive Protein Markerssupporting
confidence: 83%
“…The data suggest that various metastasis profiles exist. This has also been shown for other tumor types by other authors [75][76][77][78][79][80][81][82][83].…”
Section: Predictive Protein Markerssupporting
confidence: 83%
“…A number of proteomics studies indicated involvement of multiple regulatory mechanisms in breast tumorigenesis 3, 16–19. Among these mechanisms, there were described signaling pathways initiated by growth factors, such as EGF, transforming growth factor‐β, nerve growth factor and hepatocyte growth factor, and scaffold proteins, such as 14‐3‐3σ 17–19.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, proteomics-based approaches are advancing at a rapid pace as mass spectrometry technologies continue to evolve. While current sensitivity levels may make whole-cell proteomics approaches cumbersome, subcellular fractions are now being sequenced at the protein level with success [ 65 , 66 ]. Appropriate utilization of omics - level DNA-, RNA-, and protein-based approaches can only be expected to synergize in unraveling the mystery of the breast cancer metastasis genetic program.…”
Section: Discussionmentioning
confidence: 99%